Performance analysis of the threshold CAC strategy for multimedia traffic in wireless networks - Deniz, DZ; Mohamed, NO (IEEE Computer Soc, 2003)
Performance modeling and evaluation of the threshold call admission control (CAC) strategy in a wireless cell serving two types of customers; narrowband (n-type) customers which require I channel and wideband (w-type) customers which require b(w) greater than or equal to 1 channels is performed. The steady state probabilities, p(K) of the system for the threshold CAC strategy are computed using a modified matrix algorithmic technique. The results show that the handoff call loss probabilities can be made as small as possible with the use of appropriate threshold values for the new call attempts.
8th IEEE International Symposium on Computers and Communication (ISCC 2003) -- JUN 30-JUL 03, 2003 -- ANTALYA, TURKEY